Evaluation of Colilert-18 for Detection of Coliforms and Eschericha coli in Subtropical Freshwater - Chao, Kuo-Kuang (American Society for Microbiology, 2004)
The accuracy of Colilert-18 as a test for coliforms and Escherichia coli in subtropical freshwater was evaluated by using API 20E strips and fatty acid methyl ester analysis. The false-positive and -negative rates of detection were 7.4 and 3.5%, respectively, for E. coli and 9.6 and 6.3%, respectively, for coliforms.